Outcomes of invasive mechanical ventilation in children and adolescents hospitalized due to status asthmaticus in United States: a population based study. (May 2015) - Rampa, Sankeerth; Allareddy, Veerajalandhar; Asad, Rahimullah; Nalliah, Romesh P.; Allareddy, Veerasathpurush; Rotta, Alexandre T.
Abstract Objective: Current national estimates of and outcomes of Invasive Mechanical Ventilation (MV) in status asthmaticus (SA) are unclear. The objective of this study is to estimate the incidence and outcomes of MV in hospitalized SA children and adolescents. Methods: We used the Nationwide Inpatient Sample (NIS, 2009–2010), the largest all-payer hospital discharge database in United States. All hospitalizations (age ≤21 years) with a primary diagnosis of SA were selected. MV was identified using ICD-9-CM procedure codes. Multivariable regression analyses were used to examine the association between MV and outcomes (Length of Stay (LOS) and Hospital Charges (HC)). Results: Over the study period, of the 250 718 SA hospitalizations, MV was needed for <96 h in 0.37% hospitalizations and 0.18% had MV for ≥96 h. Complications occurred in 12.4% (30 991) of all hospitalizations with pneumonia (10.8%) being the most common. A total of 65 patients died in hospitals (the overall in-hospital mortality [IHM] rate was 0.03%). About 55 of these deaths occurred among those who had MV (4% IHM rate for those receiving MV). The mean LOS and hospital HC included without MV (2.1 d, $11 921) MV < 96 h (4.8 d, $52 201); MV > 96 h (15.6 d, $200 336). After adjustment for patient/hospital level factors, the need for MV was associated with significantly higher LOS and HC (p < 0.0001). Those who had MV<96 h (OR = 2.58, 95% CI = 1.77–3.77) or MV ≥ 96 h (OR = 6.23, 95% CI = 3.87–10.03) had higher risk of developing pneumonia. Conclusions: Although MV is infrequently needed in children and adolescents hospitalized for SA (0.55% incidence rate), it is associated with higher IHM rate and significant hospital resource utilization.